Removal of heavy metals from industrial wastewater using activated carbon made from lemon peels - Nur Amnani, Rosman (2017)
The heavy metal which is known as the toxic metal and normally caused by chemical waste, manufacturing, sewage, electroplating, mining and pharmaceuticals have been a main reason for various industrial wastewater nowadays. There are many common conventional wastewater treatment for removing of heavy metal like chemical precipitation and reverse osmosis that have been done in Malaysia. But mostly these methods are very expensive even they are commonly used. The solution to save the cost for treatment of heavy metal, there is one method which is adsorption. Adsorption method by using agriculture waste like lemon peel have been used as biosorbents to remove heavy metal from industrial wastewater. Lemon is commonly known used for culinary and non- culinary purpose but also can be used as agriculture waste which can be used as the activated carbon to remove heavy metal from industrial wastewater. In this study lemon peel have been used as the activated carbon to achieve the objective. The aim of this research is to determine the effect of size activated carbon and the effect of contact in reducing the percentage of heavy metal for cadmium and zinc. The analysis of heavy metal was determined by using the Atomic Adsorption Spectrophotometer (AAS). The lemon peels were obtained, washed and dried in the oven. Then, the peels were grounded into powder, separated into according size and burnt in furnace. Later, the activated carbon of lemon peels were tested by size of particle and effect of the contact time. The size of activated carbon used are 1.18mm, 600 micron, and powder. The contact time tested was four weeks. As the treatment conducted, the content of cadmium was reducing from week one to week four where 1.18mm removed 73% of cadmium, 600 micron removed 81% of cadmium and powder removed 92% of cadmium while the content of zinc from week one to week four reducing drastically where 1.18mm removed 83% of zinc, 600 micron removed 91% of zinc and powder removed 100% of zinc. The heavy metal of cadmium and zinc with COD reduce by week during the treatment conducted proving that longer period of contact are able to remove all organic matter in industrial wastewater.